Pengembangan Nominal Aturan Fuzzy pada Metode Fuzzy Mamdani untuk Menyeimbangkan Beban Tiga Phasa pada Saluran Distribusi Tegangan Menengah - Djagolado, Martinus W; Amirullah, Amirullah; Saidah, Saidah (Universitas Trunojoyo Madura, 2021)
The use of electrical equipment on the customer side with low voltage absorbs unbalanced power. The load unbalances in each phase will result in an unbalanced current, resulting in a phase voltage shift in the secondary coil of the 20 kV/380 V medium voltage transformer. Shifting the voltage in the distribution transformer phase, then causes the flow of current in the transformer neutral wire causing losses. This paper proposes a fuzzy logic method with the Mamdani fuzzy inference system (FIS) to balance three-phase load currents at seven feeders of 20 kV medium voltage distribution at PLN Rayon Taman Jawa-Timur. The feeders are Ngelom, Tawang Sari, Geluran, Bringin, Masangan Kulon, Palm Residence, and Pasar Sepanjang. There are three input variables used, namely the load current in phase R, phase S, and phase T respectively. There are three output variables in one FIS block, namely changes in load current in phase R, phase S, and phase T respectively. With the number of fuzzy rules as many as 509 rules, the proposed method is able to produce the lowest load current unbalance value of 1.6% at Palm Residence Feeders. The development of a nominal (number) of fuzzy rules in the Fuzzy Logic Method with FIS Mamdani is able to reduce the value of unbalance load current at the 20 kV medium voltage distribution feeder better than the method proposed by previous researchers.